The Analysis of Teacher Readiness in Implementing an AI (Artificial Intelligence) on Biology Subject at SMAN 1 Ampel - Nabila; Setyawati, Sophia Tri; Wasitohadi; Putra, Ie Johanes Juan Yutama (Fakultas Tarbiyah Institut Agama Islam Ngawi, 2025)
The development of technology , have given birth to Artificial Intelligence (AI) which has an impact on the education sector. Wise application of AI can improve more personalized learning for students. Teachers as facilitators need to master AI to carry out learning. However, there are still teachers who are not ready to adapt the development of AI in learning. This study aims to (1) Determine the readiness of Biology teachers at SMA N 1 Ampel in implementing Artificial Intelligence-based learning, (2) Determine the application of Artificial Intelligence technology in learning, (3) Determine the obstacles and solutions to the application of AI in Biology learning. This study uses a descriptive qualitative method implemented at SMAN 1 Ampel. Data collection techniques were carried out through interviews, observations and documentation. Data analysis using Milles and Huberman which includes data reduction, data presentation and drawing conclusions. The results of the study obtained a) Teachers' understanding in implementing AI and the readiness of school facilities and infrastructure in the sufficient category. b) AI has a positive impact on access to materials, but can trigger students to become dependent on AI, c) Implementation of AI in learning is still constrained by limited access to facilities and infrastructure. From this study, equal access to technology is very important to ensure meaningful learning for students. The importance of ongoing training for teachers to be able to utilize AI effectively in Biology learning.